حل مسألة قيم أولية باستخدام أسلوب المحاكاة (University of Mosul-college of Basic Education, 2007)
يعد أسلوب المحاكاة من الأدوات الحاسوبية الشائعة لتقليد وتتبع سلوك الأنظمة الحياتية المعقدة عبر تطورها مع الزمن. لقد تم تعريف متغيرات مسألة مرضية وبناء الأنموذج الرياضياتي لهذه المسألة، أما الحل العددي لهذا الأنموذج فقد تمت مقارنته مع المحاكاة الحاسوبية لعملية ماركوف التجديدية من نوع ولادة ووفاة، وتبين من خلال تفحص النتائج كفاءة أسلوب المحاكاة في وصف سلوك الأنظمة الواقعية الحياتية وعلى فترات زمنية ممتدة.The simulation technique is one of the common computational tools used to imitate and follow up complex real life systems and their development with time. Variables of a disease problem were defined and the mathematical model for this problem was constructed. The numerical solution of this model was compared with the computational simulation of Markov Renewal Process of the type ''Birth and Death''. The efficiency of simulation technique in the description of any real life system and through out extended time periods was obvious from the results.